CURRICULUMUL DIN PERSPECTIVA DIVERSITĂŢII CULTURALE - USM ADMIN (Moldova State University, 2007)
This article is dedicated to the problem of European integration, and intercultural education. In this context the interculturality has to be viewed on 2 levels: First level: the macro - represents the international synergy of different cultures for development of communicational system, forming of citizens that will correspond to the needs of a multinational community. Second level: the macro - the synergy of different cultural segments of some communities.